How do patients use antimalarial drugs? A review of the evidence. - Yeung, S; White, N (2005)
Patient adherence is a major determinant of the therapeutic response to antimalarial drugs, as most treatments are taken at home without medical supervision. With the introduction of new, effective, but more expensive antimalarials, there is concern that the high levels of efficacy observed in clinical trials may not be translated into effectiveness in the normal context of use. We reviewed available published evidence on adherence to antimalarial drugs and community drug usage; 24 studies were identified of which nine were 'intervention' studies, seven were classified as 'outcome studies', and the remainder were purely descriptive studies of antimalarial adherence. Definitions, methods, and results varied widely. Adherence was generally better when treatments were effective, and was improved by interventions focusing on provider knowledge and behaviour, packaging, and provision of correct dosages. There is insufficient information on this important subject, and current data certainly do not justify extrapolation from results with ineffective drugs to new effective treatments. Research in this area would benefit from of standardization of methodologies and the application of pharmacokinetic modelling.